Disability-Inclusive Efforts Reflected in Development Programs: A Review of Literature and Recommendations for Scaling UP - Mulina M. Cabatay; Nur Azizah (Universitas Pendidikan Ganesha, 2023)
Disability inclusion is adopted as the main strategy to address poverty among persons with disabilities. In low- and middle-income countries like Indonesia, the development disability gap is prevailing. Hence, this study aimed to analyze the most recent disability-inclusive efforts in development programs in Indonesia and to identify priorities for scaling up. This study use literature review and descriptive in nature. It employed the linear six-phased procedures of the thematic analysis approach in analyzing data. A total of 12 articles were selected through the semi-systematic method. Based on the findings, there are efforts in providing social and economic disability-inclusive opportunities, and emerging minimal opportunities for PWDs in the political arena. Social and legal protection is progressing but remains lacking in other provisions and several development endeavors had implemented strategic interventions, however, challenges persist. Several recommendations were identified which could serve as priorities for the future development agenda for local and national policymakers, implementers, and stakeholders. However, this study suggests further investigation into how the proposed recommendations from previous studies are being implemented by the public and private development sectors. Also, examining culturally appropriate and sensitive tools is necessary for translating the challenges into action to ensure the scalability, replicability, and sustainability of the country’s disability-inclusive development efforts.